Demographic, clinical, chest X-ray characteristics, and outcome of children admitted with acute bronchiolitis in the tertiary care hospital South India - Buddharaju, Chandradeve Varma B S K (Indian Journal of Child Health, 2022)
Aim and Objectives: The goal of this research was to assess the demographic, clinical, and radiological characteristics of children brought to the hospital with acute bronchiolitis. Materials and Methods: This is a prospective study of children aged 1–3 years who were admitted to a tertiary care center with acute bronchiolitis between June and August 2021. The research excludes infants <1 month. Age, sex, comorbidities, tachypnea, respiratory distress, saturations, nebulizations’, oxygen therapy, and mortality were all recorded as variables. The data were analyzed using appropriate statistical methods. Results: About 60% of the 162 children admitted with bronchiolitis are males, and 68% of the babies had been exposed to passive smoking. Cough (98%) and wheeze (91%) were the most common symptoms and signs, respectively. On chest X-rays, 73% of the children had hyperinflated lung fields and 8% had atelectasis. Out of 29 children with severe hypoxemia and respiratory failure, 25 children responded to high-flow nasal cannula or continuous positive airway pressure, and only four required intubation and invasive ventilation. In our study, there was no mortality. Conclusion: The most common reason for hospitalization among infants is acute bronchiolitis. We have significantly reduced the use of antibiotics, systemic steroids, and bronchodilators in our hospital after developing standard treatment protocols for acute bronchiolitis and strictly following them.